Alteration of mitochondrial function in arthropods during arboviruses infection: a review of the literature - Santana-Román, María E.; Ramírez-Carreto, Santos; Maycotte, Paola; Pando-Robles, Victoria (Frontiers in Physiology, 2025)
Arthropods serve as vectors for numerous arboviruses responsible for diseases worldwide. Despite their medical, veterinary, and economic significance, the interaction between arboviruses and arthropods remains poorly understood. Mitochondria in arthropods play a crucial role by supplying energy for cell survival and viral replication. Some arboviruses can replicate within arthropod vectors without harming the host. Successful transmission depends on efficient viral replication in the vector’s tissues, ultimately reaching the salivary glands for transmission to a vertebrate host, including humans, via blood-feeding. This review summarizes current knowledge of mitochondrial function in arthropods during arbovirus infection, highlighting gaps compared to studies in mammals and other pathogens relevant to arthropods. It emphasizes mitochondrial processes in insects that require further investigation to uncover the mechanisms underlying arthropod-borne transmission.